Quetiapine monotherapy in acute phase for major depressive disorder: A meta-analysis of randomized, placebo-controlled trials - Maneeton N. (BioMed Central, 2015)
Background: Schizophrenia and bipolar depression trials suggest that quetiapine may have an antidepressant effect.Objectives: This meta-analysis aimed to determine the efficacy, acceptability and tolerability of quetiapine treatment for major depressive disorder (MDD). Only the randomized controlled trials (RCTs) comparison between quetiapine and placebo were included. The authors searched such clinical trials carried out between 1991 and February 2012.Data sources: MEDLINE, EMBASE, CINHL, PsycINFO and Cochrane Controlled Trials Register were searched in February 2012. Study populations comprised adults with MDD or major depression.Study eligible criteria, participants and interventions: Eligible studies were randomized, placebo-controlled trials of quetiapine monotherapy carried out in adults with MDD and presenting endpoint outcomes relevant to: i) depression severity, ii) response rate, iii) overall discontinuation rate, or iv) discontinuation rate due to adverse events. No language restriction was applied.Study appraisal and synthesis methods: All abstracts identified by the electronic searches were examined. The full reports of relevant studies were assessed, and the data of interest were extracted. Based on the Cochrane methods of bias assessment, risks of bias were determined. The studies with two risks or less were included. The efficacy outcomes were the mean change scores of depression rating scales, the overall response rate, and the overall remission rates. The overall discontinuation rate was considered as a measure of acceptability. The discontinuation rate due to adverse events was a measure of tolerability. Relative risks (RRs) and weighted mean differences (WMDs) with 95% confidence intervals (CIs) were computed by using a random effect model.Results: A total of 1,497 participants in three RCTs were included. All trials examined the quetiapine extended-release (XR). The pooled mean change scores of the Montgomery-Asberg Depression Rating Scale (MADRS) and the Hamilton Depression Rating Scale (HAM-D) of the quetiapine-treated group were higher than those of the placebo-treated group with the WMDs (95%CI) of -3.37 (-3.95, -2.79) and -2.46 (-3.47, -1.45), respectively. All studies defined the response and remission as ≥ 50% reduction of the MADRS total score and the MADRS total score of ≤8 at endpoint, respectively. The overall response and remission rates were significantly greater in the quetiapine-treated group with RRs (95%CIs) of 1.44 (1.26, 1.64) and 1.37 (1.12, 1.68), respectively. The pooled discontinuation rate was not significantly different between groups with an RR (95%CI) of 1.16 (0.97, 1.39). The pooled discontinuation rate due to adverse event was greater in the quetiapine group with an RR (95%CI) of 2.90 (1.87, 4.48). With respect to sleep time, the pooled mean change Pittsburgh Sleep Quality Index (PSQI) scores of the quetiapine-treated group was also significantly higher than that of the placebo-treated group [WMD (95%CI) of -1.21 (-1.81, -0.61)].Limitations: Variety of quetiapine XR doses and the small number of RCTs were key limitations of this meta-analysis.Conclusions: Based on the limited evidence obtained from three RCTs, quetiapine XR is effective for adult patients with MDD. The high dropout rate due to adverse events suggests that some MDD patients may not be able to tolerate quetiapine XR. Due to the balance of its efficacy benefit and risk of side effects, as the overall discontinuation rate shown, the acceptability of this agent is not more than placebo. These results should be viewed as the very preliminary one. Further studies in this area are warranted.Implication of key findings: Quetiapine may be an alternative antidepressant. However, both risk and benefit of this agent should be taken into account for an individual patient with MDD. © 2012 Maneeton et al.; licensee BioMed Central Ltd.